English tournaments : using gamification as a learning strategy to enhance motivation and collaboration in the English Classroom. (2022)
Gamification is a strategy that applies principles of games in contexts that are not necessarily related to gaming activities, such as business, corporations, and formal education. Those principles consist primarily of the establishment of a set of rules, common objectives, and the delivery of rewards (Sailer et al., 2017). In this context, the use of gamification in the English classroom offers a rethink of the class and curricula structure. The use of distinctive elements, i.e., leaderboards, teamwork, and scoring systems instead of the more usual classwork and assessment techniques can enhance the motivation of learners (Baranek, 1996). This study stems from the implementation of a pedagogical intervention, which consisted of a series of English tournaments that faced students with tasks based on collaborative learning and gamification. The tournaments were a way to apply gamification to each class session, merging games and academic activities related to the English curriculum of tenth-grade students at the I.E.D Sorrento, articulated with the English class contents. An alternative class environment was offered, creating a space in which the students grouped with their peers and got involved into their process, making them interested and motivated to learn and practice English.